Effect of seal formation due to cattle manure application on infiltration and runoff - Rakesh K N (Department of Irrigation and Drainage Engineering, Kelappaji College of Agricultural Engineering and Technology, 2003)
The application of soil amendment is one of the major management practices in farming operations. Nowadays, the importance of manure application as a soil amendment is increasing due to the increased concern for the ecology and environment its abundance in availability and low cost. The manures are rich in organic matter content and other nutrients. It changes the physical properties of the soil. But the excess application of organic manure may lead to detrimental results due to the surface seal formation. Hence, the present study attempts to assess the effect of seal formation due to cattle manure application on infiltration and runoff. In the coarse textured soils, like sandy loam soil the infiltration rate will be reduced and runoff will be increased. But in the fine textured soils, like clay loam soil, the infiltration rate will be increased and runoff will be reduced. The contents of the nutrients like nitrogen, organic matter and total solids in the runoff water and the physical properties like bulk density will increase with the increase in manure application and rainfall intensity. Hence it was concluded that, while applying manure on the field, the rate of application of the manure can be determined only after determining the soil texture and rainfall intensity. Otherwise, the manure application will be results in pollution of nearby water bodies.